Solar Metallurgy for Sustainable Zn and Mg Production in a Vacuum Reactor Using Concentrated Sunlight - Srirat Chuayboon; Stphane Abanades (My University, 2020)
Solar carbothermal reduction of volatile metal oxides represents a promising pyro-metallurgical pathway for the sustainable conversion of both metal oxides and sunlight into metal commodities and fuels in a single process. Nevertheless, there are several scientific challenges in discovering suitable metal oxides candidates for the ease of oxygen extraction from metal oxides to enhance the reaction extent and in designing reactors for the efficient absorption of incident solar radiation to minimize losses. In this study, ZnO and MgO were considered as volatile metal oxides candidates, and their reaction behaviors were studied and compared through gas species production rate, metal oxides conversion, and yield. A solar reactor prototype was developed to facilitate solar carbothermal reduction of ZnO and MgO with different reducing agents comprising activated charcoal and carbon black. The process was operated in a batch operation mode under vacuum and atmospheric pressures to demonstrate the flexibility and reliability of this system for co-production of metals (Zn/Mg) and CO. As a result, decreasing total pressure enhanced conversion of ZnO and MgO, leading to increased Zn and Mg. However, in the case of ZnO, CO yield decreased with decreasing total pressure at the expense of favored CO2 as a result of the decrease of residence time. In contrast, CO2 formation was negligible in the case of MgO, and CO yield thus increased with decreasing pressure. Using activated charcoal as the reducing agent exhibited better conversion of both ZnO and MgO than carbon black thanks to the higher available specific surface area for chemical reactions. MgO and ZnO conversion above 97% and 78%, respectively, and high-purity Mg and Zn content were accomplished, as evidenced by the recovered products at the reactor outlet and filter containing pure metal. In addition, Mg product exhibited strong oxidation reactivity with air, thus requiring inert atmosphere for the handling of Mg-rich powders to avoid direct exposure to air.
Keywords: Carbothermic reaction; Carbon fibers; Chemical Looping and Thermochemical Processes